AI for accessibility in education: Ssystematic review of empirical research on educators' adoption factors. - Mohd Rahim, Noor Hanifah Safirah; Luqman, Azyanee; Li, Cheam Chai (International Journal of Accounting, Finance and Business, 2025)
Artificial intelligence (AI) holds immense potential to enhance accessibility in education, especially for students with learning disabilities. AI-powered solutions can break down barriers and create more equitable learning environments by providing AI tools such as personalized learning experiences, real-time captioning, and assistive technologies. However, the successful integration of AI in education depends on educators' willingness to adopt these innovative technologies. This systematic literature review aims to synthesize the empirical research on the factors influencing educators' adoption of AI for accessibility in educational settings. A comprehensive search of databases was conducted between year 2018 to 2024 which involved Scopus, Science Direct, Emerald Insight, Web of Science, and IEEE Xplore. The findings showed that perceived usefulness and ease of use of AI tools, digital competence and attitudes of educators, and institutional support are the key factors. The review also uncovered barriers such as concerns over data privacy, algorithmic bias, and the need for teacher training. The results provide valuable insights for researchers, policymakers, and educational leaders seeking to harness the power of AI to create more accessible and inclusive learning experiences. Recommendations for future research and practical implications are discussed to guide the responsible integration of AI in support of Sustainable Development Goal 4 which is ensuring quality education for all.